Diaspora impact to indigenous of Sama Dilaut in Sabah, Malaysia - Gusni Saat; Mokhtar K.; Kasim Bin Hj. Md. Mansur (2020)
Sama Dilaut is sub-ethnicity, and being a social group belong to the Sama-Bajau of Southeast Asia. Their ancestral settlement scattered along the Sulawesi-Sulu Seas in Sabah and Southern Philippines, and the eastern Indonesian archipelago. Due to the formation of the independent nation-statein the region, today they are separated into different citizens that the Philippines, Malaysia and Indonesia. In Sabah Sama-Bajau, were divided into four social categories, namely diLaut; sea-fisherman; land-agriculturaland urban. After Sabah obtained independence status in 1963, all Sama-Bajau social groups, except diLaut social type, being Malaysian nationality. The question is why the Sama Dilaut as the social category of diLaut, was excluded from Malaysian citizen? This paper identifies and discusses the effects of the diaspora to the indigenous status of Sama Dilaut in Sabah. It‟s found out diaspora factors determined the ability of Sama Dilaut to secure the citizenship. The main consequences of the diaspora factors were i) the failure of mainstream society to understanding diaspora concept of the Sama Dilaut;ii) the mainstream society has been misled Sama Dilaut as illegal immigrants and iii)identity contestation among the social groups of Sama-Bajau. This structural factor has formed the perception among the mainstream society in Malaysia that the Sama Dilaut in Sabah is illegal immigrants or the sea peoples without the country (statelessness).